A Mouse Model of Interstitial Pneumonitis Induced by Murine Cytomegalovirus Infection after Allogeneic Skin Transplantation. (2nd July 2013) - Ni, Dequn; Yu, Haiyang; Zhang, Wei; Gan, Lin; Zhao, Jiqiang; Wang, Mingli; Chen, Jason
Abstract : We investigated the effect of murine cytomegalovirus (MCMV) on interstitial pneumonia in transplant recipients in an experimental skin allograft model. Skin transplantation between C57BL/6J and BALB/c mice was performed in the presence or absence of cyclosporin A treatment. Flow cytometry showed that the number of CD4 + and CD8 + cells and the level of IFN- γ decreased significantly in the groups treated with cyclosporin A. We either mock-infected or infected the mice with MCMV by intranasal administration and monitored pathophysiological behavior and body weight. The infected mice were sacrificed at different days postinfection for histology, immunohistochemistry, and molecular biological evaluations. Interstitial pneumonitis was observed in positive control groups as well as in experimental group that received cyclosporin A, a skin transplant, and infected with the highest dose of virus (10 5 PFU). Transmission electronic microscopy demonstrated the presence of herpes virus particles. MCMV DNA and glycoprotein B were demonstrated in the epithelial cells of the lung tissue in those animals by in situ hybridization and immunohistochemistry, respectively. Our data demonstrated the establishment of a mouse model of interstitial pneumonitis via MCMV infection after allogeneic skin transplantation.